Development of E-Module Based Android for Teaching Material of Plantae Kingdom Topic - Afifah, Diana Iffatul; Rahayu, Enni Suwarsi; Anggraito, Yustinus Ulung (Journal of Biology Education, 2018)
Utilization of teaching materials with the latest innovation called mobile learning can be applied in learning using Android-based smartphones. Kingdom Plantae is a complex material so it needs effective teaching materials using Information Technology (IT). The development of IT has not been utilized as teaching materials. This study aims to develop Android-based e-module as a teaching material for the X-class students of Plantae kingdoms worthy, practical and effective materials. Research and Development (R & D) stages include identification of potential and problems, data, e-module design, e-module validation, revision I e-module design, small-scale trial, revision II e-module design, large-scale trials, final revision and product of the Android-based e-module material of Plantae kingdom. Data completion method is done by giving questionnaire of media and material validity, and questionnaire of practicality on small and wide scale test. Data analysis used descriptive percentage. The result of the research shows e-module worthy of teaching materials with material percentage of material 81,75% and media 88,46%. E-modules are practically used as teaching materials with a percentage of 83.05% scale test and 88.06% widescreen scale and e-modules with effectively average N-Gains of 0.61 (medium category). Based on these results, can get Android-based e-module can be used as a teaching material of high school students X class of Plantae kingdom.